2017
DOI: 10.1176/appi.ajp.2017.16010034
|View full text |Cite|
|
Sign up to set email alerts
|

A 5-Year Observational Study of Patients With Treatment-Resistant Depression Treated With Vagus Nerve Stimulation or Treatment as Usual: Comparison of Response, Remission, and Suicidality

Abstract: This registry represents the longest and largest naturalistic study of efficacy outcomes in treatment-resistant depression, and it provides additional evidence that adjunctive VNS has enhanced antidepressant effects compared with treatment as usual in this severely ill patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
213
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(235 citation statements)
references
References 22 publications
13
213
0
9
Order By: Relevance
“…Vagus Nerve Stimulation (VNS) has been shown to be efficacious for the long-term management of patients with treatment-resistant depression (Carreno & Frazer, 2017;Johnson & Wilson, 2018;Rush et al, 2000). A recent 5-year observational study of patients with treatment-resistant depression treated with VNS or treatment as usual has provided additional evidence that adjunctive VNS has enhanced antidepressant effects compared with treatment as usual (Aaronson et al, 2017;Rush et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Vagus Nerve Stimulation (VNS) has been shown to be efficacious for the long-term management of patients with treatment-resistant depression (Carreno & Frazer, 2017;Johnson & Wilson, 2018;Rush et al, 2000). A recent 5-year observational study of patients with treatment-resistant depression treated with VNS or treatment as usual has provided additional evidence that adjunctive VNS has enhanced antidepressant effects compared with treatment as usual (Aaronson et al, 2017;Rush et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is effective in patients with treatment‐resistant depression (TRD). Treatment‐resistant depression is an American FDA‐approved indication for VNS …”
Section: Applicationmentioning
confidence: 99%
“…Treatment-resistant depression is an American FDA-approved indication for VNS. 43 The overall effect of VNS on cognition is unclear, and many studies focus on memory. There is an evidence that VNS treatment can acutely improve memory in a short time, but there seems to be no significant improvement within the long-term treatment.…”
Section: Appli C Ati Onmentioning
confidence: 99%
“…Therefore, most third party payers do not currently reimburse for the procedure. Recent data from a 5-year, prospective, open-label, nonrandomized, observational registry study of VNS involving 795 patients showed significantly higher response (67.6% for VNS compared to 40.9% for treatment as usual) and remission (43.3% for VNS compared to 25.7% for treatment as usual) 3 . This may help change the reimbursement landscape.…”
Section: Neurotherapeutic Interventionsmentioning
confidence: 99%